Are We Missing the Circumplexity? An Examination of Love Styles. (2019) - Cassepp-Borges, Vicente; Ferrer, Emilio
Abstract: The colours of love theory is of great importance for understanding love. However, previous research on this theory did not consider the model as circular, as originally proposed. This article investigates the spatial location of items and underlying love dimensions in the Love Attitudes Scale with a large Brazilian sample of 1, 549 participants. The measure replicated the six-factor structure of previous studies ( Eros, Ludus, Storge, Mania, Agape and Pragma ), including the small correlations between factors and internal consistency. The circumplex structure, however, differed from the original theory. Multidimensional scaling showed an opposition between Ludus and Eros, as well as between Mania and Storge, suggesting a new spatial location to love styles. Based on the findings, we propose a revised reformulation of the colours of love theory using attachment theory as a framework to interpret the results.